Internalisasi Nilai-Nilai Pendidikan Etika Sosial Bagi Santri Putri Di Asrama Sains SMP Takhassus Al-Qur’an Kalibeber Wonosobo - Intan Nur Aini; Robingun Suyud El-Syam; Nur Farida (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The moral crisis has become a hot topic frequently discussed in various mass media lately. Various forms of moral crisis can be observed among different younger generations, including within the environment of Islamic boarding schools. In recent years, there has been a shift in values and behaviors among teenagers influenced by technology, social media, and cultural changes, leading to a decline in awareness of social ethics and prevailing norms in society. Through a holistic and integrated approach, social ethics education will provide understanding to female students about the importance of values such as empathy, tolerance, social responsibility, equality, and justice. This research aims to explore the concepts of social ethics values, the internalization process of social ethics education values, as well as the supporting and inhibiting factors of internalizing social ethics education values in the Al-Qur’an Specialized Boarding School of Kalibeber Wonosobo. The research method employed is qualitative to gain in-depth understanding. The findings indicate that the concept of internalizing social ethics education values for female students is a key factor in shaping noble character. The social ethics of female students in the Al-Qur’an Specialized Boarding School of Kalibeber Wonosobo is deemed positive based on their daily habits, and they have successfully addressed several issues through implemented programs, ensuring that the process of internalizing social ethics education values progresses as expected.